Atividades práticas com microscopia e o desenvolvimento de habilidades no ensino fundamental - Pagliarini, Daiane Schio (2016)
The practical activities contribute to the interest and learning in science and biology, especially when they involve research, curiosity, new materials and challenges. The investigation by microscopy can happen in practical classes in their classroom or a lab space. The production of drawings from observations can be a viable resource for the student to express thought and demonstrate understanding of concepts and phenomena. Through this feature it is also possible to promote the development of skills, especially those related to observation, interpretation and image description. Our objective was to investigate the use of this type of practical activities in primary education for the development of skills. The implementation of practical classes with observation and individual record was made possible by an alternative optical microscopy system that allows students greater independence in handling the equipment. Built pet bottle of microscopes for use in practical classes. In two classes, two sets of activities were carried out with the students; the first was called Freehand and the second oriented design. As main material, use plant cells in order to relate the practice to the content studied in class. The activities contributed to the improvement of students' skills in observation, record and image description. During the performance of activities it was possible to make several observations on the behavior of students face the challenges posed by the observation and recording of images and set some of the conditions for the success of this type of practice session.